Health Care Analysis on Myocardial Revascularization in Patients with Chronic Coronary Artery Disease: The Multicenter REVASK Study: Design and Protocol - Beckmann, Andreas; Bitzer, Eva-Maria; Lederle, Mareike; Ihle, Peter; Walker, Jochen; Marshall, Ursula; Horenkamp-Sonntag, Dirk; Schneider, Steffen; Zeymer, Uwe; for the REVASK Study Group (The Thoracic and Cardiovascular Surgeon, 2020)
Coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) are available for revascularization of coronary artery disease (CAD) with the aims to reduce cardiovascular morbidity and mortality and to improve disease-related quality of life in particular. The German National Care Guideline (NVL-cKHK) on chronic CAD recommends the establishment of so-called heart teams for decision making in myocardial revascularization to improve the quality of care. Preferred recommendations for PCI or CABG are given for different patient subgroups depending on patient characteristics, concomitant diseases, and coronary morphology. The myocardial revascularization study (REVASK) is a noninterventional cohort study on care of patients undergoing PCI or CABG based on retrospective statutory health insurance (SHI) routine data, registry data from the German Cardiac Society (DGK) resp., the German Society for Thoracic and Cardiovascular Surgery (DGTHG), combined with prospective primary data collection from health care providers and patients. The primary goal is to investigate whether and to which extent heart teams, consisting of cardiologists and cardiac surgeons, increase guideline adherence in decision making for myocardial revascularization. Ultimately the study project aims to improve patient care in terms of decision making for appropriate myocardial revascularization. Through the consistent implementation of the German National Care Guideline on chronic Coronary Artery Disease (NVL-cKHK) and the European Guidelines on myocardial revascularization, the reduction of morbidity, mortality and the reduced need for subsequent revascularization procedures are also desirable from a health economics perspective.
Keywords: coronary heart disease; coronary artery disease; quality assurance; health care research; heart team; guidelines